2016
DOI: 10.1080/19443994.2015.1079250
|View full text |Cite
|
Sign up to set email alerts
|

Interface behavior of PbO2 on pure lead and stainless steel as anode for dye degradation

Abstract: A B S T R A C TPbO 2 films are electrodeposited by the galvanostatic (G) and pulsed current (P) methods on lead and stainless steel (AS30), respectively. They are used as electrodes for electrochemical degradation of Amaranth dye. The scanning electron microscope, atomic force microscope, and X-ray diffraction analyses revealed the dominance of β-PbO 2 form in two anodes and the absence of the form tet-PbO and PbSO 4 in AS30 substrate that have more amorphous shape and less roughness (200 nm). A poor lead oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 56 publications
0
5
0
1
Order By: Relevance
“…The surface coverage for the samples was calculated from the following equation: 37 = Q/nFA 0 [6] where Q is the electrical charge transferred during CV, n is the number of the transferred electrons, F is the Faraday's constant, and A 0 is the electrode surface area, (1 cm 2 in our case). As suggested by Darabizad et al, the surface coverage serves as a criterion to analyze the electrocatalytic performance of an electrode.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The surface coverage for the samples was calculated from the following equation: 37 = Q/nFA 0 [6] where Q is the electrical charge transferred during CV, n is the number of the transferred electrons, F is the Faraday's constant, and A 0 is the electrode surface area, (1 cm 2 in our case). As suggested by Darabizad et al, the surface coverage serves as a criterion to analyze the electrocatalytic performance of an electrode.…”
Section: Resultsmentioning
confidence: 99%
“…1,2 The electrocatalytic activity of PbO 2 electrodes has been extensively explored in chemical synthesis, 3 ozone generation, 4 and treatment of waste effluents. [5][6][7][8] Lead dioxide and metal lead have gained popularity for the positive and negative electrode respectively in soluble lead flow batteries (SLFB), after major groundwork was laid by researchers in the UK. [9][10][11] The fabrication of PbO 2 coatings normally employs galvanostatic anodic deposition, conducted on an inert substrate.…”
mentioning
confidence: 99%
“…The EIS parameters listed in Table 2 were obtained from the collected experimental data fitted with the equivalent circuit (Figure 7) where R s corresponds to the solution resistance, and (R coating , Q coating ) and (R ct , Q dl ) characterize, respectively, the properties of the coating and the charge transfer process at the interface electrode/electrolyte. The Warburg impedance (W) is assigned to the diffusion of charged species [12]. It can be seen from the Nyquist plots displayed in Figure 8 that SS/PbO2 (Figure 8a) and SS/TiO2/PbO2-10%B (Figure 8c) electrodes present straight lines while SS/TiO2/PbO2 impedance spectra (Figure 8b) present a straight line with the appearance of a semi-circular shape at a high-frequency range attributed to the fast charge transfer at the anode interface [52].…”
Section: Eis Measurements and Fittingmentioning
confidence: 99%
“…The efficiency of the generated hydroxyl radicals depends mainly on the anode materials in terms of composition and morphology [10,11]. Lead dioxide (PbO 2 ) is among the widely used anodes for wastewater treatment thanks to its high electrical conductivity, good stability, low cost and long service lifetime [8,12,13]. However, the fragile binding force and the low stability of PbO 2 coating may lead to lead ions leaching during the electrolysis process, or it could even peel off of the coating from the substrate surface, affecting therefore the lifetime of the electrode and limiting its practical application [14].…”
Section: Introductionmentioning
confidence: 99%
“… 22 However, in an acidic and neutral media, PbO 2 morphology has a good correlation with the obtainment of high oxygen over potential. 23 For a further enhancement of the electrocatalytic proprieties of PbO 2 during various anodic reactions, the incorporation of metal oxide, such as TiO 2 , 24 RuO 2 , 25 CeO 2 , 26 SS/PbO 2 , 23 and ZrO 2 , 27 into lead dioxide matrix was realized. These researches have indicated that the performance of PbO 2 electrode is influenced significantly by metal oxide particles.…”
Section: Introductionmentioning
confidence: 99%